Rifampicin-induced challenges in managing endocrine hypertension and primary aldosteronism: a case report and literature review - Song, Xiaoxiao; Jia, Minyue; Yu, Hanxiao; Dong, Zhichao; Cheok, Kai; Pan, Xin (Frontiers in Pharmacology, 2025)
BackgroundPrimary Aldosteronism (PA), a form of endocrine hypertension (EH), often manifests as Resistant Hypertension (RHTN). RHTN is an increasingly prevalent clinical condition associated with target organ damage and a poor prognosis. Accurate diagnosis and management of EH and PA are challenging due to their diverse clinical manifestations, complex laboratory findings, and potential drug-drug interactions (DDIs). These DDIs, often overlooked in practice, can complicate the diagnostic and treatment processes.Case PresentationA 56-year-old man with uncontrolled hypertension was admitted to our hospital. He was suspected of having Primary Aldosteronism (PA) and subclinical Cushing’s Syndrome (SCS) based on elevated aldosterone-to-renin ratio (ARR), captopril challenge test results (CCT), and low-dose dexamethasone suppression test (LDDST) results. Adrenal CT showed mild bilateral adrenal hyperplasia. Despite being on six antihypertensive medications, including spironolactone, his blood pressure remained uncontrollable. His medical history revealed prior use of rifampicin for brucellosis. Rifampicin, a CYP450 inducer, caused drug-drug interactions (DDIs), leading to a false-positive dexamethasone suppression test (DST) and reduced efficacy of antihypertensive drugs. After discontinuing rifampicin, his blood pressure was controlled with fewer medications. One month later, repeated ARR and CCT were still positive. Adrenal venous sampling (AVS) indicated bilateral aldosterone secretion without a dominant side, confirming Idiopathic Hyperaldosteronism (IHA). Targeted treatment with MRA led to partial clinical and biochemical remission of PA.ConclusionThis case highlights the diagnostic and therapeutic challenges of Endocrine Hypertension (EH) and Primary Aldosteronism complicated by CYP450 enzyme inducers. Specifically, the use of rifampicin, a potent CYP450 inducer, resulted in false-positive diagnostic test results and diminished efficacy of antihypertensive medications, thereby contributing to RHTN. When encountering uncontrolled hypertension, particularly when standard treatments fail, awareness of DDIs is crucial for accurate diagnosis and effective management.